Pengaruh Keamanan Konsumen dan Kualitas Informasi terhadap Keputusan Pembelian pada Produk Fashion di Shopee dengan Kepercayaan sebagai Variabel Intervening - Embun Salsabiila; Muinah Fadhilah; Putri Dwi Cahyani (Journal Competency of Business, 2018)
This research was conducted to determine the effect of consumer safety and information quality on purchasing decisions through trust in fashion products in shopee. The location of this research is in Yogyakarta. The population of this research is shopee users in Yogyakarta. A sample of 100 respondents was taken using the accidential sampling technique. The data collection method used a questionnaire. The analysis used is multiple linear analysis with the results of the study showing that consumer security has a significant effect on trust, information quality has a significant effect on trust, consumer security has no significant effect on purchasing decisions, information quality has no significant effect on purchasing decisions, trust has a significant effect on consumer confidence. Security can explain the indirect relationship between consumer security and information quality with purchasing decisions.